The effect of intranasal oxytocin on social reward processing in humans: a systematic review - Kraus, Jakub; Výborová, Eliška; Silani, Giorgia (Frontiers in Psychiatry, 2023)
Understanding the neurobiology of social reward processing is fundamental, holding promises for reducing maladaptive/dysfunctional social behaviors and boosting the benefits associated with a healthy social life. Current research shows that processing of social (vs. non-social) rewards may be driven by oxytocinergic signaling. However, studies in humans often led to mixed results. This review aimed to systematically summarize available experimental results that assessed the modulation of social reward processing by intranasal oxytocin (IN-OXY) administration in humans. The literature search yielded 385 results, of which 19 studies were included in the qualitative synthesis. The effects of IN-OXY on subjective, behavioral, and (neuro)physiological output variables are discussed in relation to moderating variables—reward phase, reward type, onset and dosage, participants’ sex/gender, and clinical condition. Results indicate that IN-OXY is mostly effective during the consumption (“liking”) of social rewards. These effects are likely exerted by modulating the activity of the prefrontal cortex, insula, precuneus, anterior cingulate cortex, amygdala, and striatum. Finally, we provide suggestions for designing future oxytocin studies. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021278945, identifier CRD42021278945.